Investigation of stability of the steganographic digital watermarks embedding into vector images - Karpinets, V. V.; Yaremchuk, Yu. Ye. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Stability of the method of digital watermarks (DWs) embedding in vector images to malicious attacks, which can be subjected to vector images with built-in DWs is considered in the paper. The results showed that the method is sufficiently robust to attacks aimed at the reading, locating, removal or substitution of DWs, as well as complication of extracting the DWs holder by adding noise, removing or adding points of vector image.